THE INFLUENCE OF CADMDIUM LOAD ON THE IMMUNE STATUS OF ORGANISM OF LAYING HENS - Ostapyuk, A. Y.; Gutyj, B. V. (Scientific Progress & Innovations, 2020)
The aim of the study was to research the effect of cadmium sulfate at a dose of 2 and 4 mg/kg of body weight on the immune system of laying hens. Twenty-four Haysex white laying hens, 78 weeks of age, were selected from which three groups were formed: control and two experimental. The control group of hens was on a regular diet, fed with compound feed and drinking water without adding cadmium sulfate. For 30 days, cadmium sulfate was added to the drinking water of the hens in the experimental groups in the following doses: the first group – 2 mg/kg, the second group – 4 mg/kg of body weight. The keeping conditions and indoor microclimate parameters for all poultry groups were the same. During the experiment, the amount of feed and water consumed was calculated. While studying the values of cellular immunity indicators it was found that the number of T- and B- lymphocytes in the diseased poultry decreased throughout the experi- ment. On the 21st day of the experiment, the number of T-lymphocytes in the blood of hens in the first and second experimental groups decreased by 1.8 and 2.7 % (P<0.001), the number of B-lymphocytes – by 2.2 and 2.9 % (P<0.01). In case of cadmium load, the antimicrobial activity of the blood serum in laying hens decreased during the first days of the study, indicating a decrease in bactericidal and lysozyme activity of the blood serum in diseased poultry. On the 21st day of the experiment, the bactericidal activity of hens’ blood serum in group D1 fluctuated within 71.4±1.41 %, and lysozyme activity of the blood serum – within 5.35±0.20 %. The lowest antimicrobial activity was established on the 21st and 30th days of the experiment, where, as compared with the initial values, bactericidal activity decreased by 15.5 and 14.4 %, and lysozyme activity – by 0.95 and 0.67 %. A high level of circulating immune complexes in the blood serum of laying hens indicates the inhibition of the organism immunologic response system due to the attachment of specific antibodies to metabolism products under cadmium load. The suppression of nonspecific element of the im- mune system is manifested by a decrease in the neutrophils phagocytic activity, a decrease in phagocytic value and phagocytic index. The lowest phagocytic value was registered on the 21st day of the experiment in the two experimental groups of hens, in which this indicator decreased by 16.6 % in the first experimental group and by 18.4 % in the second experimental group of hens as compared with the control group. On the 21st day of the experiment, phagocytic activity in the blood of hens of the second experimental group made 50.6±1.46 %, which was 10.7 % lower than the values of the control group of hens.